Taxonomic status of the genus Sotalia: Species level ranking for tucuxi (Sotalia fluviatilis) and costero (Sotalia guianensis) dolphins - Caballero, S.; Trujillo, F.; Vianna, J. A.; Barrios-Garrido, H.; Montiel, M. G.; Beltran-Pedreros, S.; Marmontel, M.; Santos, M. C.; Rossi-Santos, M.; Santos, F. R.; Baker, C. S. (Blackwell Publishing, 2007)
Dolphins of the genus Sotalia are found along the Caribbean and Atlantic coasts of Central and South America and in the Amazon River and most of its tributaries. At present, the taxonomy of these dolphins remains unresolved. Although five species were described in the late 1800s, only one species is recognized currently (Sotalia fluviatilis) with two ecotypes or subspecies, the coastal subspecies (Sotalia fluviatilis guianensis) and the riverine subspecies (Sotalia fluviatilis fluviatilis). Recent morphometric analyses, as well as mitochondrial DNA analysis, suggested recognition of each subspecies as separate species. Here we review the history of the classification of this genus and present new genetic evidence from ten nuclear and three mitochondrial genes supporting the elevation of each subspecies to the species level under the Genealogical/Lineage Concordance Species Concept and the criterion of irreversible divergence. We also review additional evidence for this taxonomic revision from previously published and unpublished genetic, morphological, and ecological studies. We propose the common name costero for the coastal species, Sotalia guianensis (Van Beneden 1864), and accept the previously proposed tucuxi dolphin, Sotalia fluviatilis (Gervais, 1853), for the riverine species.
Keywords: tucuxi; mtDNA; nuclear DNA; taxonomy; Sotalia guianensis; Sotalia fluviatilis